2022
DOI: 10.17219/acem/144199
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complaints from students during COVID-19 pandemic

Abstract: Background. During coronavirus disease 2019 (COVID-19) pandemic, students were obliged to switch to online learning. Nevertheless, a long time spent in front of the screens is one of the risk factors of dry eye disease (DED).Objectives. To evaluate ocular symptoms typical for DED presented by Polish students during online learning and entertainment before and during the pandemic, as well as to assess the prevalence of these symptoms. Materials and methods.The original questionnaire was distributed online via s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…During Covid-19 pandemic several studies reported significant associtation between VD screen usage and DED among students who studied online, as well as female sex and contact lens wear [ 12 , 13 , 48 ]. Studies taken in Spain and Poland showed intensified DED symptoms among student population who studied online [ 49 , 50 ]. In addition, one study investigated the effect of face mask usage on DED during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…During Covid-19 pandemic several studies reported significant associtation between VD screen usage and DED among students who studied online, as well as female sex and contact lens wear [ 12 , 13 , 48 ]. Studies taken in Spain and Poland showed intensified DED symptoms among student population who studied online [ 49 , 50 ]. In addition, one study investigated the effect of face mask usage on DED during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%